THE INFLUENCE OF LIFESTYLE PERSONALITY FACTOR ON PURCHASING DECISIONS TO HERDI HARDCASE BANDUNG CUSTOM PRODUCTS - Herdiyani, Sankist; Safa’atul Barkah, Cecep; Chan, Arianis; Wulan Tresna, Pratami (Business Administration Department - Universitas Katolik Parahyangan, 2023)
Each individual certainly has different needs. This becomes the basis of consumer behavior in making purchasing decisions for the goods they need. One of them is about lifestyle. This study aims to determine whether lifestyle personality factors influence purchasing decisions, especially for Herdi Hardcase Bandung products. This study uses a descriptive quantitative research method. The sample of this study is determined by purposive sampling. Data analysis techniques used are validity test, reliability test, classical normality test, linearity test, simple linear regression analysis, t test, and determinant coefficient (R²) using SPSS v.26 The results of this study indicate that lifestyle personality factor has a significant effect on purchase decisions. The regression coefficient of the lifestyle variable is 26.245 and the significance is 0.003. So, the hypothesis in this research which states that lifestyle personality factor has a significant effect on the purchasing decision of Herdi Hardcase Bandung custom product is accepted.